Identifying Interventions for Improving Letter Formation: A Brief Experimental Analysis of Students with Intellectual Disabilities - E. Rüya ÖZMEN; Zehra ATBAŞI (International Electronic Journal of Elementary Education, 2016)
As a group, students with intellectual disabilities display difficulties in a wide range of academic skills, including the acquisition of basic academic skills such as literacy. Early writing and reading skills must be supported to prepare students with intellectual disabilities to learn to read and write. The goal of this study was to replicate and extend the current research on Brief Experimental Analysis with letter formation. Three students with intellectual disabilities participated in the study. A brief multi-element design was used to test effectiveness of four interventions on letter formation. These interventions included goal setting plus contingent reinforcement, graphical feedback, error correction and modeling. For one student, modeling was effective; for the two remaining students, goal setting plus contingent reinforcement was effective. The results of this study extend the BEA literature by investigating the effects of interventions for improving letter formation in students with intellectual disabilities. The study findings suggest that using BEA to assess the relative contribution of each intervention can identify the most effective interventions for improving letter formation in students with intellectual disabilities.